Analisis Strategi Digital Kewirausahaan yang Efektif Bagi Siswa Kelas 3 SMKN 2 Ambon - Rehalat, Aminah (Perspektif Pendidikan dan Keguruan, 2024)
This study aims to identify and analyze effective digital entrepreneurship strategies for grade 3 students of SMKN 2 Ambon. Using a mixed methods approach, this study combines quantitative to measure the understanding and application of digital strategies and qualitative to explore students' views on innovation, creativity, and job opportunities. Through a qualitative approach with questionnaires, FGDs, and interviews, it was found that although 75% of students had a good understanding of digital technology, only 40% applied it in entrepreneurial projects. Innovation and creativity are recognized as important, but most students feel they lack adequate skills. The results showed that most students have a good understanding of digital technology, but the application in entrepreneurial projects is still low. Innovation is recognized as an important element, although innovative skills among students are still considered inadequate. Students' creativity is more focused on marketing using social media, while product development is still limited. In addition, the majority of students are aware of job opportunities in the digital field, but feel the need for further guidance and support to take advantage of these opportunities. This study suggests the development of digital innovation and entrepreneurship skills through more structured learning and practical guidance.